Penerapan Metode Objective Matrix dan Rootcause Analysis pada Pengukuran Produktivitas Produksi Gula di PT KLM - Kamilah, Nurisma Bintang; Nugraha, Isna (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Measuring the company's productivity performance is very important to assess achievements and evaluate aspects that need to be improved. PT KLM is engaged in sugar production, trying to improve productivity which is considered unstable. This research aims to analyze productivity during the 2024 milling period and provide recommendations for improvement. The methods used are Objective Matrix and Rootcause Analysis. RCA analysis was carried out with the Five-Why method and fishbone diagram to obtain improvement recommendations that can increase productivity in the future. Based on the Five-Why analysis and fishbone diagram, the company needs to optimize productivity through increased supervision and availability of quality raw materials, provide motivation and evaluation levels to employees, and control the efficient use of machines. The results show the highest productivity value in period 6 of 636.80 and the lowest productivity occurred in the first period of 65.27. The highest productivity change index occurred in the third period with a value of 285.62%. While the lowest index of change occurred in the last period with a value of -44.85, Criteria that need to be improved include raw materials, labor and machine hours. Keywords: Fishbone Diagram, Five-Why Analysis, Omax, Productivity, RCA